Alternate load paths in mitigating progressive collapse of RC building structures subjected to column loss scenarios - Tan, Kang Hai (2011)
Column loss scenarios result in high potential for progressive collapse of RC building structures since the gravity loads are severely amplified by both doubling-of-span and dynamic factors. Under such a situation, tensile membrane action and catenary action with steel reinforcement carrying the vertical loads by acting as a kind of tensile net are the last line of defence mechanism just before the final collapse kicks in. For years, much attention has been devoted for improving these two alternate load paths in order to mitigate progressive collapse of RC building structures subjected to column loss scenarios.